Burnout Syndrome in Nursing Students Based on Effect Of Stressor, Relational Meaning and Coping Strategy - Hilda Mazarina Devi; Nursalam Nursalam; Laily Hidayati (Jurnal Ners, 2013)
Introduction: Professional education program is a program in which nursing students are transformed to become professional nurses. At this level, nursing students will encounter various stressors. The purpose of this study was to analyze the relationship between stressors, relational meaning and coping strategy on burnout syndrome in nursing students who are undergoing professional education.Method: This was a correlational study using cross-sectional approach. Population comprised regular student of nursing profession program at the Faculty of Nursing, Airlangga University. Sample size was determined by simple random sampling and 61 persons were included in the inclusion criteria. Data then analyzed using multiple linear regression test with signi fi cance level ofα < 0.05.Results: This study found that total burnout syndrome was signi fi cantly related to relational meaning (p = 0.005, β = 0.460). Emotional exhaustion was signi fi cantly related to relational meaning (p= 0.001, β = 0.532) and emotion focused coping (p = 0.035, β =0.298). Relational meaning was also signifi cantly related to depersonalization (p = 0.002, β = 0.050). Subsequently, the decline in self-achievement was signi fi cantly related to personal stressors, i.e the number of room mates (p = 0.016, β = 0.344), total learning time/day (p = 0.036, β=0.366) and environmental stressors (workload) (p = 0.039, β = -0.349). Discussion: It is suggested for students to prepare for professional education, and the Faculty of Nursing, Airlangga University, should strengthen the function of academic counselors in terms of preceptorship role model in order to avoid the risk of burnout syndrome when the nursing students undergoing professional education.